Warming Alters Hydrologic Heterogeneity: Simulated Climate Sensitivity of Hydrology‐Based Microrefugia in the Snow‐to‐Rain Transition Zone. Issue 3 (18th March 2019) - Marshall, A. M.; Link, T. E.; Abatzoglou, J. T.; Flerchinger, G. N.; Marks, D. G.; Tedrow, L.
Abstract: In complex terrain, drifting snow contributes to ecohydrologic landscape heterogeneity and ecological refugia. In this study, we assessed the climate sensitivity of hydrological dynamics in a semiarid mountainous catchment in the snow‐to‐rain transition zone. This catchment includes a distinct snow drift‐subsidized refugium that comprises a small portion (14.5%) of the watershed but accounts for a disproportionate amount (modeled average 56%) of hydrological flux generation. We conducted climate sensitivity experiments using a physically based hydrologic model to assess responses of a suite of hydrologic metrics across the watershed. Experiments with an imposed 3.5 °C warming showed reductions in average maximum snow water equivalent of 58–68% and deep percolation by 72%. While relative decreases were similar across the watershed, much greater absolute decreases in snowpack occurred in the drift‐subsidized site than the surrounding landscape. In drift‐subsidized locations, warming caused a shift from a regime that included both energy‐ and water‐limited evapotranspiration conditions to exclusively water‐limited conditions. Warming also resulted in altered interannual variability of hydrologic metrics. The drift‐subsidized unit was more sensitive to warming than the surrounding landscape, with reduced potential for the effects of warming to be offset by increased precipitation. Despite spatially homogeneous changes in climate, the effects of climate change on the hydrological dynamics were spatially heterogeneous in this watershed due to the presence of lateral water transport in the form of drifting snow. These findings suggest an increase in hydrologic homogeneity across the landscape and relatively large changes in snow drift‐subsidized refugia. Key Points: Snow drift‐subsidized hydrology‐based refugia diminished with simulated warming, creating greater hydrologic homogeneity Drift‐subsidized sites historically varied between water and energy limitation, but became exclusively water‐limited in warmer scenarios Modeled warming decreased interannual variability of peak SWE and increased variability of evapotranspiration and peak SWE timing